Aspectos reproductivos de siete especies de aves en el Bosque Chaqueño Serrano, Córdoba, Argentina - Schaaf, Alejandro A.; Peralta, Giovana; Luczywo, Ayelen; Díaz, Agustín; Peluc, Susana (Nuestras Aves, 2015)
Este artículo no cuenta con un resumen.